4-2m+4m+1=

Simple and best practice solution for 4-2m+4m+1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-2m+4m+1= equation:


Simplifying
4 + -2m + 4m + 1 = 0

Reorder the terms:
4 + 1 + -2m + 4m = 0

Combine like terms: 4 + 1 = 5
5 + -2m + 4m = 0

Combine like terms: -2m + 4m = 2m
5 + 2m = 0

Solving
5 + 2m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 2m = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 2m = 0 + -5
2m = 0 + -5

Combine like terms: 0 + -5 = -5
2m = -5

Divide each side by '2'.
m = -2.5

Simplifying
m = -2.5

See similar equations:

| 8+5y=24 | | 4*x=2.5 | | (-x+9)*4= | | 7a-20=80 | | 3(2y+5)=30 | | 23x-5=25x-5 | | 2x+5=133 | | Y=58x+228 | | 7=5k-3 | | 5x-1=-5x+1 | | 7/2*63=7/2*2/7 | | M-5=11 | | (-x+7)*3= | | (g-7)(g+9)= | | 4v=8e-g | | 10m+3=38 | | 0.9=-log | | 2*-1=0 | | -2x^2-22x+24= | | 4v=8e | | 2x+2=0.50x+11 | | 5a+12=36 | | 3n-5n=3 | | (7x-6)=90 | | 5/7x35 | | 5(2x+6)=-3(4x-1) | | 4(m-2)=14 | | (4x+3)+(-2x+4)=y | | 4.7p+8.7p+2.6p=93.96 | | 18x-36=12x-24 | | 2.2=-log(x) | | -15x+43=-10x+28 |

Equations solver categories